The Kubrawī and early Javanese Islam: Re-assessing the significance of a 16th-century Kubrawī silsila in the Sejarah Banten Ranté-Ranté. Issue 143 (2nd January 2021) - Wain, Alexander
ABSTRACT: Beyond somewhat vague allusions to Sufi influence, a qualitative sense of early Javanese Islamic praxis remains sadly lacking among scholars. This article attempts to rectify that deficiency by re-assessing the importance of a Kubrawī silsila (spiritual genealogy) found within the 17th- to early 18th-century Javanese chronicle, Sejarah Banten Ranté-Ranté . First identified by Martin van Bruinessen in 1994, this silsila preserves detailed information about two separate Sunni-orientated Kubrawī lineages attributable to the latter's Central Asian sub-branch, the Hamadānī. Set within the context of other early Javanese Muslim texts containing previously overlooked evidence of Kubrawī praxis, in addition to hagiographical traditions identifying one Jumadil Kubra (a probable cypher for Kubrawī founder, Najm al-Dīn al-Kubrā) as the island's earliest Muslim practitioner and a resident of Gresik, we argue that this silsila indicates considerable Kubrawī influence over Java's initial Islamisation. Further consideration of the silsila 's specific Hamadānī characteristics set against wider 13th- to 15th-century Islamic history suggests either a north Indian or, more probably, Sino-Muslim origin for that influence. We therefore conclude by interpreting the Sejarah Banten silsila as a possible window onto the substantive nature of Sino-Muslim involvement in early Javanese Islam, adding further nuance to our understanding of that island's Islamisation.